POSSIBILITIES OF PREVENTION AND REDUCTION OF THREATS AFFECTING THE SAFETY AND FLUIDITY OF LAND TRANSPORT - Josef Reitšpís; Martin Mašľan (Baltic Journal of Economic Studies, 2021)
Ensuring mobility and the necessary volume of transportation is one of the basic conditions for the functioning of the economy. The potential threat to existing transport systems is therefore an area that needs increased attention. The complexity of modern transportation is due to its increasing frequency, the expansion of transport routes, as well as the increase in the number of actors involved in their implementation, which places ever greater demands on their mutual coordination. It is necessary to constantly monitor the progress of transportation, to identify and assess the risks that may affect them. Insufficient attention to this issue can lead to time and material losses, in the worst case, the death of their participants, or to the high financial costs required to rebuild the disrupted system. Transport is an open system in which more and more people are working, whether transported or involved in its organization, which increases the possibility of their failure and facilitates the possibility of attack. Strict application of risk management, assessment and, if necessary, implementation of necessary measures can lead to protection of high-value assets. At present, we already commonly encounter concepts such as the intelligent transport route or the autonomous means of transport. All these circumstances, as well as the importance of transport, which we could compare to blood circulation of the state's economy, make it a possible target for various types of attacks. Cyber threats and attacks are becoming more and more relevant today. Such an attack is characterized by a relatively low level of threat to the attacker himself and a possible high level of damage if it is successful.